2019
DOI: 10.1111/cns.13265
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone polarizes microglia and protects against pilocarpine‐induced status epilepticus

Abstract: Aims Activated microglia have been found in the forebrains and hippocampi of temporal lobe epilepsy (TLE) patients and status epileptic (SE) animal models. The peroxisome proliferator‐activated receptor γ (PPAR γ) agonist rosiglitazone has been shown to prevent microglial activation. However, its role in pilocarpine‐induced status epilepticus remains unknown. We aimed to examine the effect of the PPAR γ agonist rosiglitazone in protecting against pilocarpine‐induced status epileptic resulting from over‐activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…The inflammatory response following status epilepticus causes activation of inducible nitric oxide synthase (iNOS) and iNOS-derived nitric oxide (NO) reacts with O 2 - to form the peroxynitrite and contributes the severity of oxidative stress in kainic-acid induced experimental status epilepticus in our previous studies [ 25 , 26 , 27 , 28 ]. Several studies with a various animal model of status epilepticus such as pilocarpine-induced, pentylenetetrazole-induced, diisopropylfluorophosphate, lithium-pilocarpine model, also demonstrated the critical role of NO-related pathway and neuro-inflammation contributing to neuronal damage [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory response following status epilepticus causes activation of inducible nitric oxide synthase (iNOS) and iNOS-derived nitric oxide (NO) reacts with O 2 - to form the peroxynitrite and contributes the severity of oxidative stress in kainic-acid induced experimental status epilepticus in our previous studies [ 25 , 26 , 27 , 28 ]. Several studies with a various animal model of status epilepticus such as pilocarpine-induced, pentylenetetrazole-induced, diisopropylfluorophosphate, lithium-pilocarpine model, also demonstrated the critical role of NO-related pathway and neuro-inflammation contributing to neuronal damage [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Influencing microglia/macrophage (please add/macrophage here) polarization to the M2 phenotype has been proposed as a possible strategy in the treatment of neurological disorders 27–31 . In this study, we found that the protective effect of EP on WMI may be associated with microglia polarization toward M2 and subsequent increase in the expression of antiinflammatory related molecules and suppression of pro‐inflammatory factors.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, we also found that HFS in the MS could exert antiseizure effect in acute seizure models, but could not drive hippocampal theta rhythm, which indicated that the other mechanisms may be involved in antiseizure effect of HFS in the MS. As HFS is generally inhibitory, we hypothesized that the antiseizure effect of HFS at MS might be mediated by the inhibition of pro‐seizure MS glutamatergic neurons 27 . Moreover, apart from the modulation of neural activities, the antiseizure effect of DBS might also be related with the neuroinflammation and microglia polarization, which has been implicated in epilepsy 54,55 . Although electrical stimulation is not cell specific compared with optogenetic intervention, DBS may be easier to have a clinical translation for epilepsy treatment.…”
Section: Discussionmentioning
confidence: 99%